2020
DOI: 10.3390/s20236713
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Trained Deep Convolutional Neural Network for Clostridioides Difficile Bacteria Cytotoxicity Classification Based on Fluorescence Images

Abstract: Clostridioides difficile infection (CDI) is an enteric bacterial disease that is increasing in incidence worldwide. Symptoms of CDI range from mild diarrhea to severe life-threatening inflammation of the colon. While antibiotics are standard-of-care treatments for CDI, they are also the biggest risk factor for development of CDI and recurrence. Therefore, novel therapies that successfully treat CDI and protect against recurrence are an unmet clinical need. Screening for novel drug leads is often tested by manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Many researches conduct a comparison of CNN transfer learning to solve classification problems. Brodzicki et al [6] conduct research for bacteria classification and make the comparison of VGG-19, ResNet50, Xception, and DenseNet121. Talo et al [7] solve Multiclass Histopathology Image Classification using DenseNet-161 and ResNet-50 pre-trained.…”
Section: Related Workmentioning
confidence: 99%
“…Many researches conduct a comparison of CNN transfer learning to solve classification problems. Brodzicki et al [6] conduct research for bacteria classification and make the comparison of VGG-19, ResNet50, Xception, and DenseNet121. Talo et al [7] solve Multiclass Histopathology Image Classification using DenseNet-161 and ResNet-50 pre-trained.…”
Section: Related Workmentioning
confidence: 99%
“…Machine vision/computer vision, known as a subset of artificial intelligence (AI), is mainly used for problems with image and video recognition, image analysis and classification, media recreation, recommendation systems, natural language processing, etc. [ 33 , 34 , 35 , 36 ]. Convolutional neural networks (CNN) are a deep-learning-based robust algorithm to fulfill machine vision tasks.…”
Section: An Overview Of Software Used To Analyze An Image or Videomentioning
confidence: 99%
“…One or more fully connected layers, also called dense layers, connect every input to every output by a learnable weight. The whole process is explained as features from an image/video extracted in the convolution layer, and then it is down sampled by pooling layers; they are then mapped by a subset of fully connected layers to create the final outputs of the network, such as the probabilities for each class in classification tasks [ 34 , 35 , 36 ].…”
Section: An Overview Of Software Used To Analyze An Image or Videomentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental result showed that this method had a better effect in diagnosing skin lesions [ 13 ]. Brodzicki et al trained a convolutional neural network model to classify Clostridioides difficile bacteria cytotoxicity using transfer learning methods and achieved a classification accuracy rate of 93.5% on 369 images, with excellent recognition [ 14 ].…”
Section: Introductionmentioning
confidence: 99%